Barriers to Successful Implementation of Total Productive Maintenance (TPM) and Ways to Overcome Them - Guimaraes, Helder (2004)
In this research I investigate the barriers encountered during implementation of TPM – Total Productive Maintenance – and possible remedies in order to overcome these obstacles. The object of the investigation is a Japanese manufacturing firm with operations in Malaysia and the central focus of the present case study cover the definitions, general principles and rationale of TPM, the intended benefits of deploying the maintenance technique and the problems in following a TPM plan, preceding the identification of possible remedies that management can apply in converting those hurdles into surmountable tasks at the shop floor. My findings include the characterisation of two potentially major barriers to the implementation of TPM. The first concerns what I classify as “generational-skills gap” among production and maintenance personnel in manufacturing organisations and the second point relates to concerns derived from implementing TPM by utilising complex Information Technology (IT) solutions.